Toxic Stress as a Potential Factor Inducing Negative Emotions in Parents of Newborns and Infants with Cyanotic Congenital Heart Disease - Grażyna Cepuch; Agnieszka Kruszecka-Krówka; Anna Lalik; Agnieszka Micek (MDPI AG, 2023)
Background: Parents who have a newborn with a congenital heart defect experience negative emotions, which may determine the emotional state of their children. Methods: The study group included 154 parents of newborns and infants with cyanotic congenital heart disease, before cardiac surgery and after the procedure. HADS m and PSS-10 questionnaires were used to assess parental anxiety, depression, aggression, and the level of stress. Results: High levels of depression, anxiety, total HADS and stress were diagnosed in a large group of parents, regardless of the stage of cardiac surgery treatment. A high level of stress was associated with a higher prevalence of emotional disturbance both in the total HADS (overall) and in all its individual domains. Anxiety and depression were more common in mothers. A high level of stress was a significant predictor of anxiety and depression in parents. Conclusions: A high level of stress was a significant predictor of anxiety and depression in parents of infants with congenital heart disease. The parents' psychological condition is one of many potential determinants over the course of their child's treatment and recovery.